Improved Endurance of Ferroelectric Hf0.5Zr0.5O2 Using Laminated-Structure Interlayer - Meiwen Chen; Shuxian Lv; Boping Wang; Pengfei Jiang; Yuanxiang Chen; Yaxin Ding; Yuan Wang; Yuting Chen; Yan Wang (Nanomaterials, 2023)
In this article, the endurance characteristic of the TiN/HZO/TiN capacitor was improved by the laminated structure of a ferroelectric Hf0.5Zr0.5O2 thin film. Altering the HZO deposition ratio, the laminated-structure interlayer was formed in the middle of the HZO film. Although small remanent polarization reduction was observed in the capacitor with a laminated structure, the endurance characteristic was improved by two orders of magnitude (from 106 to 108 cycles). Moreover, the leakage current of the TiN/HZO/TiN capacitor with the laminated-structure interlayer was reduced by one order of magnitude. The reliability enhancement was proved by the Time-Dependent Dielectric Breakdown (TDDB) test, and the optimization results were attributed to the migration inhibition and nonuniform distribution of oxygen vacancies. Without additional materials and a complicated process, the laminated-structure method provides a feasible strategy for improving HZO device reliability.